THE EFFECT OF GENOCISM IN ISLAMIC EDUCATION THOUGHT - Imron Bima Saputra; M. Fajri Syahroni Siregar (Proceeding International Seminar of Islamic Studies, 2021)
This study is very interesting to study, starting from the background that discusses the emergence of the understanding of Sufism or genocism among Muslims which was marked in the 8th to 13th century Masehi. Sufism or genocism it self is an understanding of getting closer to Allah Swt so as to get happiness in this world and the akhirat. The methodology in this research is descriptive qualitative, with historical approaches and other related sources. From the results of this research, it can be found about: the development of genocism in the realm of Islamic thought, monumental figures and works, the division of Sufism, traces of genocism in Islamic education thought and the influence of Genocism in Islamic education thought.Keywords:The Effect, Genocisme, Islamic Education Thought